2009
DOI: 10.1089/hum.2008.213
|View full text |Cite
|
Sign up to set email alerts
|

Pressure-Mediated Transfection of Murine Spleen and Liver

Abstract: Extension of in vivo nucleic acid transfection techniques and increased information about those transfection properties and side effects are urgently needed to advance biological research and drug therapy. Tissue pressure-mediated transfection, involving lightly pressing the target tissue after intravenous injection of plasmid DNA or small-interfering RNA (siRNA), is a promising approach because of its high transfection efficiency and resulting low tissue damage. In this study, the gene expression/silencing pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
32
1

Year Published

2010
2010
2014
2014

Publication Types

Select...
7
1

Relationship

6
2

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 31 publications
1
32
1
Order By: Relevance
“…Previous studies demonstrated that the degree of pressure could be used to control the expression levels of the transfected plasmid DNA (pDNA). [9][10][11] Regarding kidneys in mice, renal dysfunction 8) and secretion of proinflammatory cytokines 9) were not observed under the experimental conditions of the tissue pressure method. Recently, Oba et al transfected the miR-200 family of microRNA to mice kidneys via the tissue pressure method and reported that that transfection ameliorated renal tubulointerstitial fibrosis in the mice.…”
Section: -7)mentioning
confidence: 88%
See 1 more Smart Citation
“…Previous studies demonstrated that the degree of pressure could be used to control the expression levels of the transfected plasmid DNA (pDNA). [9][10][11] Regarding kidneys in mice, renal dysfunction 8) and secretion of proinflammatory cytokines 9) were not observed under the experimental conditions of the tissue pressure method. Recently, Oba et al transfected the miR-200 family of microRNA to mice kidneys via the tissue pressure method and reported that that transfection ameliorated renal tubulointerstitial fibrosis in the mice.…”
Section: -7)mentioning
confidence: 88%
“…[8][9][10] In this method, the target organs of the mice are pressed directly after intravenous injection (i.v.) of the naked nucleic acids.…”
Section: -7)mentioning
confidence: 99%
“…10) We have investigated tissue pressure-mediated transfection in order to develop a naked plasmid DNA transfection method with a high gene transfection efficiency and which causes little tissue injury. 11,12) This transfection is performed by light and controlled pressure of the target tissue after normal intravenous injection of plasmid DNA. It is a development that is based on the phenomena described by Liu and Huang in their pioneering report where liver-specific gene expression could be obtained without liver toxicity by massaging the abdomen after intravenous injection of plasmid DNA in mice.…”
mentioning
confidence: 99%
“…10) We have been successful in quantitatively controlling the degree of pressure on tissues, and have suggested that plasmid DNA and small-interfering RNA (siRNA) are very efficiently transfected into the murine kidney, liver and spleen without marked tissue damage and this includes an increase in biomarker and pro-inflammatory cytokine production. 11,12) Understanding the key physiological phenomena affecting transgene expression is very important for the proper use of this method and to allow improvements to be made. In general, there are many barriers to gene expression following administration of plasmid DNA: biodistribution, cellular and nuclear translocation of plasmid DNA and transcription and translation.…”
mentioning
confidence: 99%
“…38,39) As more mild physical stimuli, pressure-mediated transfections of intravenously delivered naked pDNA to the kidney, liver and spleen have been reported. 40,41) Moreover, tissue suction using a device enables site-specific transfection by naked pDNA to the kidney, liver, spleen, and heart. 42) On the other hand, rubbing stimuli against the gastric serosal surface greatly enhanced naked pDNA transfer.…”
Section: Other Physical Stimulimentioning
confidence: 99%